دور التسويق السياحي في دعم التنمية السياحية و الحد من أزمات القطاع السياحي - رشيد, فراح; يوسف, بودلة (Recherches économiques et managériales; Vol. 12 (2012): RECHERCHES ÉCONOMIQUES ET MANAGÉRIALES (DÉCEMBRE))
يصنف القطاع السياحي ضمن قطاع الخدمات، لكنه يختلف عن بقية الأنشطة الخدمية الأخرى، كون النشاط السياحـي منتج مركب، يتشكل من سلع مادية و غير مادية، لذلك تم تصنيفه ضمن الخدمات المختلفة، فهو يشترك في بعض خصائصه مع الخصائص العامة للخدمات، بالإضافة إلى وجود خصائص أخرى تميزه عن باقي الخدمات. و يعتبر التسويق السياحي عاملا مهما في تحقيق التنمية السياحية، نظرا لما يقوم به من دور في التعريف و الترويج للمنتج السياحي، و إقناع العملاء بزيادة طلبهم على المنتجات السياحية. كما تمثل التنمية السياحية مختلف البرامج التي تهدف إلى تحقيق الزيادة المستقرة و المتوازنة في الموارد السياحية، و تعميق و ترشيد الإنتاجية في القطاع السياحي. و هي تمثل بالتالي هدفا تسعى إليه المؤسسات الخدمات السياحية، و سنتطرق خلال هاته الورقة البحثية إلى إبراز الدور الذي يكتسيه التسويق السياحي في دعم و تطوير التنمية السياحية، و كذا الحد من الأزمات التي يواجهها القطاع السياحي. الكلمات المفتاحية : السياحة، التسويق السياحي، المزيج التسويقي السياحي، التنمية السياحية، أزمات القطاع السياحي.                                                       Abstract Classifies the tourism sector with the services sector, but it differs from the rest of the activities of other services, the fact that tourism product compound, is formed from material goods and non-material, so it has been classified within the various services, he shares some characteristics with the general characteristics of services, as well as to the existence of properties further distinguish it from other services. The tourism marketing is an important factor in achieving the development of tourism, given for his role in the definition and promotion of the tourism product, and convinces customers to increase their demand on tourism products. It also represents the tourism development of various programs aimed at achieving balanced and stable increase in tourism resources, and deepens and streamlines productivity in the tourism sector. And is therefore a goal sought by the institutions of tourism services. We will look through the following paper to highlight the role that tourism marketing in support of tourism development, and as well as reducing the crises faced by the tourism sector. Keywords : Tourism, Tourism marketing, Tourism marketing mix, Tourism development, Crises of the tourism sector.